Pseudomelanosis Duodeni after Intravenous Iron Supplementation in a Patient with Multiple Comorbidities: A Case Report - Olanrewaju Adeniran; Ayowumi Andrew Adekolu; Joshua Kirkpatrick; Ethan M. Cohen; Abdullahi Adedotun Sulaiman; Farirai Marwizi; Zachary Kovac; Budoor Alqinai; Raja Samir Khan (Case Reports in Gastroenterology)
Introduction: Pseudomelanosis duodeni (PD) is a rare condition characterized by multiple pigmented speckles in the duodenum. It is typically seen in adults and has been associated with chronic kidney disease, hypertension, iron deficiency anemia, diabetes mellitus, and the use of medications like oral iron, hydralazine, furosemide, and hydrochlorothiazide. While oral iron is common, only one documented PD has been associated with intravenous (IV) iron supplementation. Case Presentation: A 69-year-old female with multiple comorbidities, including stage 4 chronic kidney disease and hypertension, presented with persistent nausea and vomiting. An esophagogastroduodenoscopy (EGD) revealed diffuse, dark speckling throughout the duodenal mucosa. Biopsies confirmed PD through Perl Prussian blue and Fontana-Masson staining, which detected iron in black/brown pigmentations within macrophages. The patient received a 5-week course of weekly intravenous iron supplementation 6 months before presentation. Previous EGD 7 and 5 years earlier showed no evidence of PD despite the patient being on sulfur-containing antihypertensive medications. This case suggests a likely interplay between IV iron and sulfur-containing medications in PD development. Conclusion: While PD has been associated with multiple comorbidities and certain medications, the causal mechanism remains unclear. PD likely entails defective iron transport and iron sulfide accumulation within duodenal macrophages. This case highlights the potential role of IV iron supplementation in PD development, even in the absence of oral iron intake. PD is regarded as a benign condition with no specific guidelines for treatment or follow-up, but a biopsy is crucial to rule out other differential diagnoses and avoid unwanted interventions.